2001
DOI: 10.1002/fld.165
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of Navier–Stokes equations using multiquadric radial basis function networks

Abstract: SUMMARYA numerical method based on radial basis function networks (RBFNs) for solving steady incompressible viscous flow problems (including Boussinesq materials) is presented in this paper. The method uses a 'universal approximator' based on neural network methodology to represent the solutions. The method is easy to implement and does not require any kind of 'finite element-type' discretization of the domain and its boundary. Instead, two sets of random points distributed throughout the domain and on the bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 17 publications
2
53
0
Order By: Relevance
“…For the approximation of a function and its derivatives, the numerical example above indicated that the indirect approach performs well for a wide range of β. In solving second order DEs (Mai-Duy and Tran-Cong [16]), experience…”
Section: High Order Odesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the approximation of a function and its derivatives, the numerical example above indicated that the indirect approach performs well for a wide range of β. In solving second order DEs (Mai-Duy and Tran-Cong [16]), experience…”
Section: High Order Odesmentioning
confidence: 99%
“…Sharan et al [13]; Zerroukat et al [14]; Mai-Duy and Tran-Cong [15,16]; Fedoseyev et al [17] based on a differential process (Kansa [12]) and the indirect approach (IRBF) based on an integration process (Mai-Duy and Tran-Cong [15,18]). Both approaches were tested on the solution of second order DEs and the indirect approach was found to be superior to the direct approach (Mai-Duy and Tran-Cong [15]).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last twenty years, radial-basis-function networks (RBFNs) have been developed to solve different types of differential problems encountered in applied mathematics, science and engineering (e.g. [1,2,3,4,5,6,7,8,9]). …”
Section: Introductionmentioning
confidence: 99%
“…In [4,5,6,7,8], the RBF approximations are constructed using integration (integrated RBFNs (IRBFNs)) rather than the usual differentiation. This approach has the ability to overcome the problem of reduced convergence rates caused by differentiation and to provide effective ways to implement derivative boundary values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation